2020
DOI: 10.1080/21501203.2020.1711826
|View full text |Cite
|
Sign up to set email alerts
|

SEM and qRT-PCR revealed quercetin inhibits morphogenesis of Aspergillus flavus conidia via modulating calcineurin-Crz1 signalling pathway

Abstract: Aspergillus flavus exploits diverse mechanisms to survive during exposure to antifungal agents including morphogenesis. Germination of dormant conidia involves cascades of reactions integrated into the signalling pathway. This study documents the effect of phytochemical-quercetin on A. flavus during germination of conidia using scanning electron microscopy (SEM). Significant inhibition of conidial swelling of A. flavus in comparison to control was observed at 4 and 7 h Quantitative real-time PCR for genes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Higher levels of calcium kinase, cAMP, Rhogdp, Plc and Pkc encoding genes were observed in groups treated with quercetin. Thus, the data suggested the antifungal potential of quercetin [ 29 ].…”
Section: Properties Of Quercetinmentioning
confidence: 99%
“…Higher levels of calcium kinase, cAMP, Rhogdp, Plc and Pkc encoding genes were observed in groups treated with quercetin. Thus, the data suggested the antifungal potential of quercetin [ 29 ].…”
Section: Properties Of Quercetinmentioning
confidence: 99%
“…The hyaline conidial heads of A. flavus and globose to sub‐globose vesicles with conidia was also observed by Zakaria, (2018) using SEM. Another study by Shishodia, Tiwari, Hoda, Vijayaraghavan, & Shankar, (2020) also reported microscopic features of A. flavus using SEM analysis. The morphological features of A. flavus were also observed by Li et al (2022) in their study.…”
Section: Discussionmentioning
confidence: 95%
“…In A. parasiticus , not only is crzA important in elevated calcium levels tolerance, but it also performs an essential function in aflatoxin biosynthesis, as deleted crzA mutants have a shallow ability (if any) to produce the toxin [ 79 ]. In A. flavus , it was reported that quercetin upregulates both calcineurin and crz1/crzA genes, upregulation that was interpreted as a response to quercetin-induced stress [ 80 ]. In A. niger , CrzA deletion results in lower biofilm formation, decreased adhesion and hydrophobicity of conidia, decreased hyphae flocculation ability, and altered cell wall integrity of the hyphae [ 53 ].…”
Section: Other Targets From the Calcineurin Pathwaymentioning
confidence: 99%